2021
DOI: 10.3389/fpls.2021.740936
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Fruit-Detection Algorithm for Edge Computing Applications

Abstract: In recent years, deep-learning-based fruit-detection technology has exhibited excellent performance in modern horticulture research. However, deploying deep learning algorithms in real-time field applications is still challenging, owing to the relatively low image processing capability of edge devices. Such limitations are becoming a new bottleneck and hindering the utilization of AI algorithms in modern horticulture. In this paper, we propose a lightweight fruit-detection algorithm, specifically designed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…This variation of weight size influences the tested real-time detection of model to support the claim of Lawal [ 8 ]. Apart from Mask-RCNN unable to meet the less than 50 ms standard of real-time detection proposed by Zhang et al [ 40 ], all YOLO-related models were able to achieve this standard as shown in Table 2 . YOLOv5-LiNet and YOLOv5-LiNetC having the same detection time of 2.6 ms is faster than 55.6 ms of Mask-RCNN, 2.8 ms of YOLOv5n, 3.4 ms of YOLOv5-Efficientlite, 3.5 ms of YOLOv5-MobileNetv3, 2.9 ms of YOLOv5-GhostNet, 2.9 ms of YOLOv5-LiNetBiFPN but slower than 2.4 ms of YOLOv5-LiNetFPN, 2.4 ms of YOLOv5-ShuffleNetv2 and 2.2 ms of YOLOv4-tiny.…”
Section: Resultsmentioning
confidence: 91%
“…This variation of weight size influences the tested real-time detection of model to support the claim of Lawal [ 8 ]. Apart from Mask-RCNN unable to meet the less than 50 ms standard of real-time detection proposed by Zhang et al [ 40 ], all YOLO-related models were able to achieve this standard as shown in Table 2 . YOLOv5-LiNet and YOLOv5-LiNetC having the same detection time of 2.6 ms is faster than 55.6 ms of Mask-RCNN, 2.8 ms of YOLOv5n, 3.4 ms of YOLOv5-Efficientlite, 3.5 ms of YOLOv5-MobileNetv3, 2.9 ms of YOLOv5-GhostNet, 2.9 ms of YOLOv5-LiNetBiFPN but slower than 2.4 ms of YOLOv5-LiNetFPN, 2.4 ms of YOLOv5-ShuffleNetv2 and 2.2 ms of YOLOv4-tiny.…”
Section: Resultsmentioning
confidence: 91%
“…The results from Tab.24 and 25 illustrate that RTNet attached with ResNet-18/CSPNet, which are widely used backbones in CV [76], [77], [78], [79], [80], and self-attention, which is widely used module in NLP [81], [82], [83], share similar and promising performances. These indicate that RTNet not only has splendid adaptability but also has great potential to couple with SOTA architectures in other AI fields.…”
Section: E4 Ablation Studymentioning
confidence: 99%
“…To reduce the computational complexity and improve the speed of deep learning architectures number of models has been proposed such as Mobile Net, MobileNetv2, ShuffleNetv1 and ShuffleNetv2, Yolo tiny series etc., As fruit size in the actual environment is variable, these networks are unable to predict small size fruits with small number of layers. A Light model with edge devices Light-CSP Net has been proposed 158 to overcome this issue. In the structure of Light-CSP Net down sampling layer with cross scale fusion replaced the maximum pooling layer and FPN is replaced with deep shallow layer.…”
Section: Fruit Feature Extraction Using Deep Learning Approachesmentioning
confidence: 99%